1999
DOI: 10.1002/(sici)1522-2586(199911)10:5<861::aid-jmri35>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

4D magnetic resonance velocity mapping of blood flow patterns in the aorta in young vs. elderly normal subjects

Abstract: Four-dimensional magnetic resonance MR velocity mapping was developed to study normal flow patterns in the thoracic aorta using time-resolved cardiac gated threedirectional velocity data. Sixteen normal subjects were studied, one young group (average age 31 years) and one group with elderly people (average age 72 years). Blood flowed in a right-handed helix from the ascending aorta to the aortic arch. A straight flow pattern or a left-handed helix was seen in the descending aorta. Blood flow was never paraboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
108
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(127 citation statements)
references
References 0 publications
15
108
1
3
Order By: Relevance
“…Findings from previous qualitative analyses of flow patterns showed righthanded helical flow patterns in the AAo and left-handed helicity in the DAo (17,19,20,23,38). Our data suggests that this helicity, which is derived from the in-plane component of the flow direction, is reflected by the distribution of WSS circ as shown in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Findings from previous qualitative analyses of flow patterns showed righthanded helical flow patterns in the AAo and left-handed helicity in the DAo (17,19,20,23,38). Our data suggests that this helicity, which is derived from the in-plane component of the flow direction, is reflected by the distribution of WSS circ as shown in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…6a. In this case, previously reported methods relying on in-plane velocity measurements and evaluation of PWV along a vessel centerline (29)(30)(31)(32)(33)(34) are no longer applicable. Note also that the complex aortic shape and in particular the sharp bending of the distal descending aorta in this patient (see Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, more comprehensive three-dimensional (3D) CINE techniques in combination with three-directionally encoded velocities (flow-sensitive four-dimensional [4D] MRI) have been reported that provide information on multidirectional in vivo blood flow with full volumetric coverage of the vessel of interest (29)(30)(31)(32)(33)(34). It was the purpose of this study to investigate if PWV can be reliably estimated from 3D CINE PC data despite its lower temporal resolution by exploiting its full volumetric coverage.…”
mentioning
confidence: 99%
“…Hence, in several 2D throughplane PC studies of maximum velocity and flow determinations in stenotic vessels, a multi-slice procedure was used [11,20]. With the advent of three-dimensional, three-directional velocity encoding sequences (here denoted 4D PC) [21][22][23], the possibility has emerged to quantify velocity and flow in multiple 4 dimensions, and in addition to visualize blood flow by streamlines and pathlines. These powerful possibilities offered by 4D PC have found a number of applications, and 4D PC has started to go beyond a visualization tool into a quantitative technique for extraction of velocity, flow and hemodynamically derived parameters such as wall shear stress [24] and kinetic energy [25].…”
Section: An Alternative Non-invasive Methods For Blood Velocity Measurmentioning
confidence: 99%